A grey-DEMATEL approach for analyzing factors critical to the implementation of reverse logistics in the pharmaceutical care process - de Campos, Elaine Aparecida Regiani; Tavana, Madjid; ten Caten, Carla Schwengber; Bouzon, Marina; de Paula, Istefani Carísio (Environmental Science and Pollution Research)

An integrated information fusion and grey multi-criteria decision-making framework for sustainable supplier selection - Aslani, Babak; Rabiee, Meysam; Tavana, Madjid (International Journal of Systems Science: Operations & Logistics)

A Systematic Review of Organizational Factors Impacting Cloud-based Technology Adoption Using Technology-Organization-Environment Framework - Al Hadwer, Ali; Tavana, Madjid; Gillis, Dan; Rezania, Davar (Internet of Things)

An inventory-location optimization model for equitable influenza vaccine distribution in developing countries during the COVID-19 pandemic - Rastegar, Mehdi; Tavana, Madjid; Meraj, Afshin; Mina, Hassan (Vaccine)

An Integrated Fuzzy Goal Programming—Theory of Constraints Model for Production Planning and Optimization - Zare, Habib; Kamali Saraji, Mahyar; Tavana, Madjid; Streimikiene, Dalia; Cavallaro, Fausto (Sustainability)

A common weights model for investigating efficiency-based leadership in the russian banking industry - Kazemi, Sajad; Tavana, Madjid; Toloo, Mehdi; Zenkevich, Nikolay A. (RAIRO - Operations Research)

A simulation–optimization model for solving flexible flow shop scheduling problems with rework and transportation - Gheisariha, Elmira; Tavana, Madjid; Jolai, Fariborz; Rabiee, Meysam (Mathematics and Computers in Simulation)

A joint chance-constrained data envelopment analysis model with random output data - Khanjani Shiraz, Rashed; Tavana, Madjid; Fukuyama, Hirofumi (Operational Research)

A Dynamic Decision Support System for Sustainable Supplier Selection in Circular Economy - Alavi, Behrouz; Tavana, Madjid; Mina, Hassan (Sustainable Production and Consumption)

An integrated quality and resilience engineering framework in healthcare with Z-number data envelopment analysis - Tavana, Madjid; Nazari-Shirkouhi, Salman; Farzaneh Kholghabad, Hamidreza (Health Care Management Science)

An integrated fuzzy framework for analyzing barriers to the implementation of continuous improvement in manufacturing - Tavana, Madjid; Shaabani, Akram; Valaei, Naser (International Journal of Quality & Reliability Management)

A fuzzy maturity-based method for lean supply chain management assessment - Soares, Gabriela Pereira; Tortorella, Guilherme; Bouzon, Marina; Tavana, Madjid (International Journal of Lean Six Sigma)

A robust cross-efficiency data envelopment analysis model with undesirable outputs - Tavana, Madjid; Toloo, Mehdi; Aghayi, Nazila; Arabmaldar, Aliasghar (Expert Systems with Applications)

Four research pathways for understanding the role of smart technologies in accounting - Mancini, Daniela; Lombardi, Rosa; Tavana, Madjid (Meditari Accountancy Research)

A new non-radial directional distance model for data envelopment analysis problems with negative and flexible measures - Tavana, Madjid; Izadikhah, Mohammad; Toloo, Mehdi; Roostaee, Razieh (Omega)

The Cologne Picture Naming Test for Language Mapping and Monitoring (CoNaT): An Open Set of 100 Black and White Object Drawings - Weiss Lucas, Carolin; Pieczewski, Julia; Kochs, Sophia; Nettekoven, Charlotte; Grefkes, Christian; Goldbrunner, Roland; Jonas, Kristina (Frontiers in Neurology)
Language assessment using a picture naming task crucially relies on the interpretation of the given verbal response by the rater. To avoid misinterpretations, a language-specific and linguistically controlled set of unambiguous, clearly identifiable and common object–word pairs is mandatory. We, here, set out to provide an open-source set of black and white object drawings, particularly suited for language mapping and monitoring, e.g., during awake brain tumour surgery or transcranial magnetic stimulation, in German language. A refined set of 100 black and white drawings was tested in two consecutive runs of randomised picture order and was analysed in respect of correct, prompt, and reliable object recognition and naming in a series of 132 healthy subjects between 18 and 84 years (median 25 years, 64% females) and a clinical pilot cohort of 10 brain tumour patients (median age 47 years, 80% males). The influence of important word- and subject-related factors on task performance and reliability was investigated. Overall, across both healthy subjects and patients, excellent correct object naming rates (97 vs. 96%) as well as high reliability coefficients (Goodman–Kruskal's gamma = 0.95 vs. 0.86) were found. However, the analysis of variance revealed a significant, overall negative effect of low word frequency ( p < 0.05) and high age ( p < 0.0001) on task performance whereas the effect of a low educational level was only evident for the subgroup of 72 or more years of age ( p < 0.05). Moreover, a small learning effect was observed across the two runs of the test ( p < 0.001). In summary, this study provides an overall robust and reliable picture naming tool, optimised for the clinical use to map and monitor language functions in patients. However, individual familiarisation before the clinical use remains advisable, especially for subjects that are comparatively prone to spontaneous picture naming errors such as older subjects of low educational level and patients with clinically apparent word finding difficulties.

Improving the efficacy and reliability of rTMS language mapping by increasing the stimulation frequency - Nettekoven, Charlotte; Pieczewski, Julia; Neuschmelting, Volker; Jonas, Kristina; Goldbrunner, Roland; Grefkes, Christian; Weiss Lucas, Carolin (Human Brain Mapping)
Abstract Repetitive TMS (rTMS) with a frequency of 5–10 Hz is widely used for language mapping. However, it may be accompanied by discomfort and is limited in the number and reliability of evoked language errors. We, here, systematically tested the influence of different stimulation frequencies (i.e., 10, 30, and 50 Hz) on tolerability, number, reliability, and cortical distribution of language errors aiming at improved language mapping. 15 right‐handed, healthy subjects (m = 8, median age: 29 yrs) were investigated in two sessions, separated by 2–5 days. In each session, 10, 30, and 50 Hz rTMS were applied over the left hemisphere in a randomized order during a picture naming task. Overall, 30 Hz rTMS evoked significantly more errors (20 ± 12%) compared to 50 Hz (12 ± 8%; p <.01), whereas error rates were comparable between 30/50 and 10 Hz (18 ± 11%). Across all conditions, a significantly higher error rate was found in Session 1 (19 ± 13%) compared to Session 2 (13 ± 7%, p <.05). The error rate was poorly reliable between sessions for 10 (intraclass correlation coefficient, ICC = .315) and 30 Hz (ICC = .427), whereas 50 Hz showed a moderate reliability (ICC = .597). Spatial reliability of language errors was low to moderate with a tendency toward increased reliability for higher frequencies, for example, within frontal regions. Compared to 10 Hz, both, 30 and 50 Hz were rated as less painful. Taken together, our data favor the use of rTMS‐protocols employing higher frequencies for evoking language errors reliably and with reduced discomfort, depending on the region of interest.

Confinement Effects for Efficient Macrocyclization Reactions with Supported Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes - Ziegler, Felix; Kraus, Hamzeh; Benedikter, Mathis J.; Wang, Dongren; Bruckner, Johanna R.; Nowakowski, Michał; Weißer, Kilian; Solodenko, Helena; Schmitz, Guido; Bauer, Matthias; Hansen, Niels; Buchmeiser, Michael R. (ACS Catalysis)
For entropic reasons, the synthesis of macrocycles via olefin ring-closing metathesis (RCM) is impeded by competing acyclic diene metathesis (ADMET) oligomerization. With cationic molybdenum imido alkylidene N-heterocyclic carbene (NHC) complexes confined in tailored ordered mesoporous silica, RCM can be run with macrocyclization selectivities up to 98% and high substrate concentrations up to 0.1 M. Molecular dynamics simulations show that the high conversions are a direct result of the proximity between the surface-bound catalyst, proven by extended X-ray absorption spectroscopy, and the surface-located substrates. Back-diffusion of the macrocycles decreases with decreasing pore diameter of the silica and is responsible for the high macrocyclization efficiency. Also, Z-selectivity increases with decreasing pore diameter and increasing Tolman electronic parameter of the NHC. Running reactions at different concentrations allows for identifying the optimum substrate concentration for each material and substrate combination.
Keywords: Catalysis; General Chemistry

Rh(I)/(III)‐N‐Heterocyclic Carbene Complexes: Effect of Steric Confinement Upon Immobilization on Regio‐ and Stereoselectivity in the Hydrosilylation of Alkynes - Panyam, Pradeep K. R.; Atwi, Boshra; Ziegler, Felix; Frey, Wolfgang; Nowakowski, Michał; Bauer, Matthias; Buchmeiser, Michael R. (Chemistry – A European Journal)
Rh(I) NHC and Rh(III) Cp* NHC complexes (Cp*=pentamethylcyclopentadienyl, NHC=N-heterocyclic carbene=pyrid-2-ylimidazol-2-ylidene (Py−Im), thiophen-2-ylimidazol-2-ylidene) are presented. Selected catalysts were selectively immobilized inside the mesopores of SBA-15 with average pore diameters of 5.0 and 6.2 nm. Together with their homogenous progenitors, the immobilized catalysts were used in the hydrosilylation of terminal alkynes. For aromatic alkynes, both the neutral and cationic Rh(I) complexes showed excellent reactivity with exclusive formation of the β(E)-isomer. For aliphatic alkynes, however, selectivity of the Rh(I) complexes was low. By contrast, the neutral and cationic Rh(III) Cp* NHC complexes proved to be highly regio- and stereoselective catalysts, allowing for the formation of the thermodynamically less stable β-(Z)-vinylsilane isomers at room temperature. Notably, the SBA-15 immobilized Rh(I) catalysts, in which the pore walls provide an additional confinement, showed excellent β-(Z)-selectivity in the hydrosilylation of aliphatic alkynes, too. Also, in the case of 4-aminophenylacetylene, selective formation of the β(Z)-isomer was observed with a neutral SBA-15 supported Rh(III) Cp* NHC complex but not with its homogenous counterpart. These are the first examples of high β(Z)-selectivity in the hydrosilylation of alkynes by confinement generated upon immobilization inside mesoporous silica.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Immobilized Platinum Hydride Species as Catalysts for Olefin Isomerizations and Enyne Cycloisomerizations - Maier, Sarah; Cronin, Steve P.; Vu Dinh, Manh-Anh; Li, Zheng; Dyballa, Michael; Nowakowski, Michał; Bauer, Matthias; Estes, Deven P. (Organometallics)
Platinum hydride species catalyze a number of interesting organic reactions. However, their reactions typically involve the use of high loadings of noble metal and are difficult to recycle, making them somewhat unsustainable. We have synthesized surface-immobilized Pt–H species via oxidative addition of surface OH groups to Pt(PtBu3)2 (1), a rarely used immobilization technique in surface organometallic chemistry. The hydride species thus made were characterized by infrared, magic-angle spinning nuclear magnetic resonance, and X-ray absorption spectroscopies and catalyzed both olefin isomerization and cycloisomerization of a 1,6 enyne (5) with a high selectivity and low Pt loading.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry

Fundamental Characterization, Photophysics and Photocatalysis of a Base Metal Iron(II)‐Cobalt(III) Dyad - Huber-Gedert, Marina; Nowakowski, Michał; Kertmen, Ahmet; Burkhardt, Lukas; Lindner, Natalia; Schoch, Roland; Herbst‐Irmer, Regine; Neuba, Adam; Schmitz, Lennart; Choi, Tae‐Kyu; Kubicki, Jacek; Gawelda, Wojciech; et al. (Chemistry – A European Journal)
Keywords: Photocatalytic Hydrogen Production; Catalysis; Inorganic Chemistry

Work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and their impact on cultural participation - Flath, Beate; Momen Pour Tafreshi, Maryam (Arts and the Market)
Purpose The purpose of this article is to illuminate the relations of work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and barriers and needs of vulnerable customers (VC) in order to explore possibilities to increase cultural participation of VC. Design/methodology/approach This article explores work-related practices of managers of live music events in OWL and asks if and to what extent these practices have an influence on the cultural participation of “vulnerable customers” (VC). It combines the findings of two studies: a) an explorative investigation on the work-related self-conceptions of managers of live music events in OWL (Study 1), and b) a sub-project on cultural participation of VC, which is part of the research project “kulturPreis. Increasing cultural participation through innovative and economically sustainable pricing concepts”, funded by the German Federal Ministry of Education and Research (Study 2). Findings It can be stated that there is an imbalance of knowledge: while VC tend to have a clear understanding of which barriers are the responsibility of managers of live music events, managers tend to lack knowledge regarding the needs of VC, and regarding the interrelationships between financial and social barriers facing them. Whether this knowledge and understanding can be developed in the future depends on the possibilities of exchanges between managers of live music events, cultural institutions, welfare organisations, political institutions and not least VC. Originality/value Based on these studies, this article combines different approaches by linking work-related practices of managers of live music events with cultural participation of VC.

Digitale Stille. Über die Bedeutung von Universitäten und Wissenschaft in der Covid-19-Pandemie - Flath, Beate (Das HEFT. Das Paderborner Veranstaltungs- und Kulturmagazin)

Data-Based Co-Creation and Participation: Reflections on an Ambivalent Relation by the Example of Music Apps - Flath, Beate (Pop – Power – Positions. Globale Beziehungen und populäre Musik (~Vibes – The IASPM D-A-CH Series 1)

Das Besondere und das Allgemeine in musikdidaktischen Kontexten. - Klingmann, Heinrich (Musikalische Bildung. Didaktik - Lehrerinnen- und Lehrerbildung - Theorie. Festschrift für Werner Jank.)

Doing Popkultur. - Klingmann, Heinrich; Ahlers, Michael (Musik-Didaktik. Praxishandbuch für die Sekundarstufe 1 und 2)

Textsortengeschichte - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Das „geheime Europa“. Hugo von Hofmannsthals späte Parallelaktion zu Stefan Georges „geheimem Deutschland“ (1919–1923) - Heise, Tillmann („Sehnsucht nach dem Leben“. Tradition und Innovation im Werk Hugo von Hofmannsthals)

Das ‚Erfundene Gespräch‘ als transatlantischer Dialog. Gattungsvariationen und Gedankenexperimente in Hofmannsthals Gesprächsfragment "Brief ans Dial" (1925) - Heise, Tillmann (Hofmannsthal-Jahrbuch)

Verfreundete Europäer im Kampf mit der Moderne - Heise, Tillmann; Beßlich, Barbara (Ruperto Carola Forschungsmagazin)

A mathematical programming approach for equitable COVID-19 vaccine distribution in developing countries - Tavana, Madjid; Govindan, Kannan; Nasr, Arash Khalili; Heidary, Mohammad Saeed; Mina, Hassan (Annals of Operations Research)

Kriterien der Sanktionierung einer Verletzung der Bonitätsprüfungspflicht - Bartlitz, David (Neue Juristische Wochenschrift (NJW))

Zum Anscheinsbeweis bei der Verwendung von Zahlungskarten mit PIN und zur Pflicht zur Sperranzeige. Anmerkung zu OLG Bremen, Beschl. v. 19.05.2021 - 1 W 4/21 - Bartlitz, David (Entscheidungen zum Wirtschaftsrecht (EWiR))

Ärger vor der Registereintragung - Bartlitz, David (Juristische Arbeitsblätter (JA))

Kooperatives Lernen von Lehramtsstudierenden im Zusammenhang mit ihrer Qualifizierung für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule – Schlussfolgerungen und Implikationen. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne

Melina Mercouri "Ich bin Griechin" (Είμαι Ρωμιά) - Janus, Richard (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Musik als Lebensmittel - Janus, Richard; Keuchen, Marion (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Themenpredigt: Reformation mit Beuys feiern - Janus, Richard (Reformation mit Joseph Beuys feiern. 31. Oktober 2021)

Reformation mit Joseph Beuys feiern. 31. Oktober 2021

Zeichen der Gemeinschaft und Begegnung. Göttliche Dreieinigkeit in der Orthodoxie - Janus, Richard

Dritte Internationale Summer School: "Formation of Faith and Trust" - Janus, Richard

Untersuchung der mechanischen und geometrischen Eigenschaften von Bauteilen hergestellt im Fused Deposition Modeling Verfahren - Knoop, Frederick
Im Rahmen dieser Arbeit wird das additive Fertigungsverfahren Fused Deposition Modeling (FDM) hinsichtlich der erzielbaren Bauteilqualität untersucht. Der Fokus liegt auf den mechanischen und geometrischen Eigenschaften für Bauteile aus ABS-M30. Hierzu erfolgt eine grundlegende Eruierung aller Einflussfaktoren auf die Bauteilqualität. Die Einflussfaktoren, die von besonderer Bedeutung sind, werden mithilfe von experimentellen Untersuchungen genauer analysiert. Ein wichtiges Merkmal im FDM-Prozess ist die Temperatur und die Luftströmung im Bauraum der Fertigungsmaschine, sodass neben der Ermittlung des Istzustandes auch eine Optimierung dieser erarbeitet wird. In den weiteren Hauptkapiteln wird neben dem Einfluss der Temperatur und Luftströmung auch der Einfluss der Strangablagestrategie untersucht. Die Strangablagestrategie kann zu einer gezielten Verbesserung der mechanischen Eigenschaften von FDM-Bauteilen genutzt werden. Die Einflüsse der Strangablagestrategie auf die geometrischen Bauteileigenschaften werden in Form von Maß- und Formabweichungen ermittelt. Ein weiteres Ziel dieser Arbeit ist die grundlegende Analyse über die Ursache von Maßabweichungen an FDM-Probekörpern. Zur Reduzierung der auftretenden Maßabweichungen, wird eine Methode erarbeitet, die zur Bestimmung von optimierten Schwindungsfaktoren dient. Die optimierten Schwindungsfaktoren werden genutzt, um die Maßabweichungen an FDM-Bauteilen maßgeblich zu reduzieren.

Oberflächennachbehandlung beim Fused Deposition Modeling – Analyse der Oberflächenstruktur und mechanischer Kennwerte - Fischer, Matthias
Mit seiner Eignung für den Einsatz in Luftfahrzeugen stellt vor allem der Werkstoff Ultem 9085 in Verbindung mit der Verarbeitbarkeit im Fused Deposition Modeling (FDM) Prozesses ein großes Potential für die Kleinserienfertigung mittels additiver Fertigungstechnologien im Luftfahrtbereich dar. Hier bestehen aufgrund der Schichtbauweise Herausforderungen zur Optimierung der Oberflächenqualität. Des Weiteren ist das Ermüdungsverhalten von FDM-Strukturen noch unzureichend erforscht. Mit dem Schwerpunkt auf dem Werkstoff Ultem 9085 sind im Rahmen dieser Dissertation zunächst Nachbehandlungsmethoden zur Verbesserung der Oberflächenqualität analysiert worden. Hier konnten Oberflächenrauheiten durch den Einsatz eines chemischen Nachbehandlungsprozesses um bis zu 80 % reduziert werden. Die dabei als Nebeneffekt erzeugte Schließung der porösen Oberflächenstruktur begünstigte zudem einen anschließenden Metallisierungsprozess zur Veredelung der Oberflächenstruktur. Die Ermüdungseigenschaften fallen für FDM-Strukturen aufgrund der inneren und äußeren Kerben im Vergleich zu spritzgegossenen Substraten vergleichsweise gering aus. Durch Überfüllung der Bau-teile und gezielte Strangorientierungen kann die Lebensdauer insbesondere für seitlich und flach aufgebaute Zugprüfkörper erhöht werden. Der chemische Nachbehandlungsprozess wirkt sich durch die Reduzierung von äußeren Kerben vor allem positiv auf die mechanischen Eigenschaften von aufrecht hergestellten Strukturen aus.

Beyond words: Children’s multimodal responses during word learning with a social robot - Tolksdorf, Nils Frederik; Mertens, Ulrich J. (International Perspectives on Digital Media and Early Literacy)
Digital devices such as social robots are increasingly being developed as artificially intelligent learning tools that could support and expand early childhood education by providing new ways to engage children in social interaction. Given this potential, research in child-robot interaction has begun to investigate which aspects of a robot’s behavior provide advantages within the interaction. However, a perspective that addresses the child’s communicative behavior within a child-robot interaction is seldom explored. In this chapter, the results of a long-term child-robot study with preschool children are presented, in which children’s multimodal response behavior during a word learning task with a social robot was in focus. The results reveal that children not only used different communicative multimodal signals such as gestures or delay markers when interacting with the robot, but also changed their behavior over the course of the sessions. The findings suggest that children shape their responses to a robot in a manifold multimodal way beyond verbal lexical utterances. Finally, implications for future child-robot interaction research, as well as identifying issues that will need to be resolved for social robots to be helpful and responsive in interaction with young learners, are discussed.

Forcierte Form

Additive Leichtbaustrukturen für die Flugzeugkabine - Menge, Dennis; Klippstein, Sven Helge; Schmid, Hans-Joachim

Kompetenzförderung im Laborpraktikum - Sacher, Marc; Bauer, Anna (Labore in der Hochschullehre. Didaktik, Digitalisierung, Organisation)

Studentische Akzeptanz und Relevanzwahrnehmung eines disziplinspezifischen Workshops „Wissenschaftliche Vorträge in der Physik“ - Bauer, Anna; Sacher, Marc; Brassat, Katharina (hochschullehre)

Entwicklung eines Bewertungsmodells zur handlungsorientierten Messung experimenteller Kompetenz (Physik)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung)

Bewertungsmodell zur experimentellen Performanz (Physik)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen)

Überlegungen auf dem Weg zu einer Theorie lehrbezogenen Wandels an Hochschulen - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Die Frage, wie sich die Weiterentwicklung der Lehre an Hochschulen systematisch verankern lässt, erfährt mit dem Auslaufen von Förderprogrammen wie dem QPL erneute Aufmerksamkeit. Bislang fehlt es an einer kontextspezifischen Theorie, die lehrbezogenen Wandel an Hochschulen analysier- und gestaltbar macht. In jedem Fall sind Change-Konzepte aus dem betriebswirtschaftlichen Bereich nur sehr beschränkt auf Hochschulen übertragbar. Demgegenüber gibt neuere Forschung Hinweise darauf, welche Kernkategorien eine hochschulspezifische Change- Theorie umfassen könnte. Darauf aufbauend schlägt der Beitrag zwei Konzepte als Kernkategorien einer Theorie lehrbezogenen Wandels an Hochschulen vor.
Keywords: educational development; change management; educational innovation

Analytical characterization of polyamide 11 used in the context of selective laser sintering: Physico-chemical correlations - Scherer, Beate; Kottenstedde, Ingo Leonard; Bremser, Wolfgang; Matysik, Frank-Michael (Polymer Testing)

HOBBIT: A platform for benchmarking Big Linked Data - Röder, Michael; Kuchelev, Denis; Ngonga Ngomo, Axel-Cyrille (Data Sci.)

Squirrel - Crawling RDF Knowledge Graphs on the Web - Röder, Michael; de Souza, Geraldo; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2020 - 19th International Semantic Web Conference, Athens, Greece, November 2-6, 2020, Proceedings, Part II)

Applying edge-counting semantic similarities to link discovery: scalability and accuracy - Georgala, Kleanthi; Ahmed Sherif, Mohamed; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 15th International Workshop on Ontology Matching co-located with the 19th International Semantic Web Conference {(ISWC} 2020), Virtual conference (originally planned to be in Athens, Greece), November 2, 2020)

Analysis of DTLS Implementations Using Protocol State Fuzzing - Fiterau-Brostean, Paul; Jonsson, Bengt; Merget, Robert; de Ruiter, Joeri; Sagonas, Konstantinos; Somorovsky, Juraj (29th USENIX Security Symposium (USENIX Security 20))

LIGON - link discovery with noisy oracles - Ahmed Sherif, Mohamed; Dreßler, Kevin; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 15th International Workshop on Ontology Matching co-located with the 19th International Semantic Web Conference {(ISWC} 2020), Virtual conference (originally planned to be in Athens, Greece), November 2, 2020)

Tentris - A Tensor-Based Triple Store - Bigerl, Alexander; Conrads, Felix; Behning, Charlotte; Ahmed Sherif, Mohamed; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2020 - 19th International Semantic Web Conference, Athens, Greece, November 2-6, 2020, Proceedings, Part I)

LIGER - link discovery with partial recall - Georgala, Kleanthi; Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 15th International Workshop on Ontology Matching co-located with the 19th International Semantic Web Conference {(ISWC} 2020), Virtual conference (originally planned to be in Athens, Greece), November 2, 2020)

NABU - Multilingual Graph-Based Neural RDF Verbalizer - Moussallem, Diego; Gnaneshwar, Dwaraknath; Castro Ferreira, Thiago; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2020 - 19th International Semantic Web Conference, Athens, Greece, November 2-6, 2020, Proceedings, Part I)

Revealing Secrets in SPARQL Session Level - Zhang, Xinyue; Wang, Meng; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille; Qi, Guilin; Wang, Haofen (The Semantic Web - ISWC 2020 - 19th International Semantic Web Conference, Athens, Greece, November 2-6, 2020, Proceedings, Part I)

Benchmarking the Lifecycle of Knowledge Graphs - Röder, Michael; Ahmed Sherif, Mohamed; Saleem, Muhammad; Conrads, Felix; Ngonga Ngomo, Axel-Cyrille (Knowledge Graphs for eXplainable Artificial Intelligence: Foundations, Applications and Challenges)

Generating Explanations in Natural Language from Knowledge Graphs - Moussallem, Diego; Speck, René; Ngonga Ngomo, Axel-Cyrille (Knowledge Graphs for eXplainable Artificial Intelligence: Foundations, Applications and Challenges)

The Semantic Web - 17th International Conference, ESWC 2020, Heraklion, Crete, Greece, May 31-June 4, 2020, Proceedings

Joint Proceedings of Workshops AI4LEGAL2020, NLIWOD, PROFILES 2020, QuWeDa 2020 and SEMIFORM2020 Colocated with the 19th International Semantic Web Conference (ISWC 2020), Virtual Conference, November, 2020

Proceedings of the SeMantic AnsweR Type prediction task (SMART) at ISWC 2020 Semantic Web Challenge co-located with the 19th International Semantic Web Conference (ISWC 2020), Virtual Conference, November 5th, 2020

A Physical Embedding Model for Knowledge Graphs - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (CoRR)

Benchmarking Knowledge Graphs on the Web - Röder, Michael; Ahmed Sherif, Mohamed; Saleem, Muhammad; Conrads, Felix; Ngonga Ngomo, Axel-Cyrille (CoRR)

Knowledge Graphs - Hogan, Aidan; Blomqvist, Eva; Cochez, Michael; d'Amato, Claudia; de Melo, Gerard; Gutiérrez, Claudio; Emilio Labra Gayo, José; Kirrane, Sabrina; Neumaier, Sebastian; Polleres, Axel; Navigli, Roberto; Ngonga Ngomo, Axel-Cyrille; et al. (CoRR)

Semantic-based End-to-End Learning for Typhoon Intensity Prediction - M. Zahera, Hamada; Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (CoRR)

Template-based Question Answering using Recursive Neural Networks - G. Athreya, Ram; Kona Bansal, Srividya; Ngonga Ngomo, Axel-Cyrille; Usbeck, Ricardo (CoRR)

Convolutional Complex Knowledge Graph Embeddings - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (CoRR)

I-AID: Identifying Actionable Information from Disaster-related Tweets - M. Zahera, Hamada; Jalota, Rricha; Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (CoRR)

Revealing Secrets in SPARQL Session Level - Zhang, Xinyue; Wang, Meng; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille; Qi, Guilin; Wang, Haofen (CoRR)

NABU - Multilingual Graph-based Neural RDF Verbalizer - Moussallem, Diego; Gnaneshwar, Dwaraknath; Castro Ferreira, Thiago; Ngonga Ngomo, Axel-Cyrille (CoRR)

Storage, Indexing, Query Processing, and Benchmarking in Centralized and Distributed RDF Engines: A Survey - Ali, Waqas; Saleem, Muhammad; Yao, Bin; Hogan, Aidan; Ngonga Ngomo, Axel-Cyrille (CoRR)

SeMantic AnsweR Type prediction task (SMART) at ISWC 2020 Semantic Web Challenge - Mihindukulasooriya, Nandana; Dubey, Mohnish; Gliozzo, Alfio; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille; Usbeck, Ricardo (CoRR)

Reflexe der immateriellen und materiellen Kultur (bislang 6 Bände, Herausgebertätigkeit Reihe)

Westfalen in der Vormoderne. Studien zur mittelalterlichen und frühneuzeitlichen Landesgeschichte (bislang 32 Bände, Herausgebertätigkeit Reihe)

Politica et Ars. Interdisziplinäre Studien zur politischen Ideen- und Kulturgeschichte (bislang 26 Bände, Herausgebertätigkeit Reihe)

Paderborner Historische Forschungen (bislang 18 Bände, Herausgebertätigkeit Reihe)

Non-adiabatic transitions in the reaction of fluorine with methane - Zhao, Bin; Manthe, Uwe (The Journal of Chemical Physics)
Keywords: pc2-ressources

Hybrid density functional theory benchmark study on lithium manganese oxides - Eckhoff, Marco; Blöchl, Peter E.; Behler, Jörg (Physical Review B)
Keywords: pc2-ressources

Multistable circular currents of polariton condensates trapped in ring potentials - Barkhausen, Franziska; Schumacher, Stefan; Ma, Xuekai (Optics Letters)
Keywords: pc2-ressources

Externally controlled Lotka-Volterra dynamics in a linearly polarized polariton fluid - Pukrop, Matthias; Schumacher, Stefan (Physical Review E)
Keywords: pc2-ressources

Learning Choice Functions via Pareto-Embeddings - Pfannschmidt, Karlson; Hüllermeier, Eyke (Lecture Notes in Computer Science)

Efficient Forward-Secure Threshold Public Key Encryption - Kurek, Rafael (Information Security and Privacy - 25th Australasian Conference, ACISP 2020, Perth, WA, Australia, November 30 - December 2, 2020, Proceedings)

Efficient Forward-Secure Threshold Signatures - Kurek, Rafael (Advances in Information and Computer Security - 15th International Workshop on Security, IWSEC 2020, Fukui, Japan, September 2-4, 2020, Proceedings)

Minimizing crane times in pre-marshalling problems - Parreño-Torres, Consuelo; Alvarez-Valdes, Ramon; Ruiz, Rubén; Tierney, Kevin (Transportation Research Part E: Logistics and Transportation Review)
Keywords: pc2-ressources

Hyper-parameterized Dialectic Search for Non-linear Box-Constrained Optimization with Heterogenous Variable Types - Sellmann, Meinolf; Tierney, Kevin (Lecture Notes in Computer Science)
Keywords: pc2-ressources

A genetic algorithm for finding realistic sea routes considering the weather - Kuhlemann, Stefan; Tierney, Kevin (Journal of Heuristics)
Keywords: pc2-ressources

Zeitschrift für deutsche Philologie (Herausgebertätigkeit von Norbert Otto Eke ab Bd. 123, 2004)

Towards a Scalable and Flexible Simulation and Testing Environment Toolbox for Intelligent Microgrid Control - Bode, Henrik; Heid, Stefan Helmut; Weber, Daniel; Hüllermeier, Eyke; Wallscheid, Oliver (arXiv:2005.04869)
Micro- and smart grids (MSG) play an important role both for integrating renewable energy sources in conventional electricity grids and for providing power supply in remote areas. Modern MSGs are largely driven by power electronic converters due to their high efficiency and flexibility. Nevertheless, controlling MSGs is a challenging task due to highest requirements on energy availability, safety and voltage quality within a wide range of different MSG topologies. This results in a high demand for comprehensive testing of new control concepts during their development phase and comparisons with the state of the art in order to ensure their feasibility. This applies in particular to data-driven control approaches from the field of reinforcement learning (RL), whose stability and operating behavior can hardly be evaluated a priori. Therefore, the OpenModelica Microgrid Gym (OMG) package, an open-source software toolbox for the simulation and control optimization of MSGs, is proposed. It is capable of modeling and simulating arbitrary MSG topologies and offers a Python-based interface for plug & play controller testing. In particular, the standardized OpenAI Gym interface allows for easy RL-based controller integration. Besides the presentation of the OMG toolbox, application examples are highlighted including safe Bayesian optimization for low-level controller tuning.

ProConAR: A Tool Support for Model-based AR Product Configuration - Gottschalk, Sebastian; Yigitbas, Enes; Schmidt, Eugen; Engels, Gregor (Human-Centered Software Engineering. HCSE 2020)
Mobile shopping apps have been using Augmented Reality (AR) in the last years to place their products in the environment of the customer. While this is possible with atomic 3D objects, there is is still a lack in the runtime conﬁguration of 3D object compositions based on user needs and environmental constraints. For this, we previously developed an approach for model-based AR-assisted product conﬁguration based on the concept of Dynamic Software Product Lines. In this demonstration paper, we present the corresponding tool support ProConAR in the form of a Product Modeler and a Product Conﬁgurator. While the Product Modeler is an Angular web app that splits products (e.g. table) up into atomic parts (e.g. tabletop, table legs, funnier) and saves it within a conﬁguration model, the Product Conﬁgurator is an Android client that uses the conﬁguration model to place diﬀerent product conﬁgurations within the environment of the customer. We show technical details of our ready to use tool-chain ProConAR by describing its implementation and usage as well as pointing out future research directions.
Keywords: Product Configuration; Augmented Reality; Model-based; Tool Support

Every Node for Itself: Fully Distributed Service Coordination - Schneider, Stefan Balthasar; Klenner, Lars Dietrich; Karl, Holger (IEEE International Conference on Network and Service Management (CNSM))
Modern services consist of modular, interconnected components, e.g., microservices forming a service mesh. To dynamically adjust to ever-changing service demands, service components have to be instantiated on nodes across the network. Incoming flows requesting a service then need to be routed through the deployed instances while considering node and link capacities. Ultimately, the goal is to maximize the successfully served flows and Quality of Service (QoS) through online service coordination. Current approaches for service coordination are usually centralized, assuming up-to-date global knowledge and making global decisions for all nodes in the network. Such global knowledge and centralized decisions are not realistic in practical large-scale networks. To solve this problem, we propose two algorithms for fully distributed service coordination. The proposed algorithms can be executed individually at each node in parallel and require only very limited global knowledge. We compare and evaluate both algorithms with a state-of-the-art centralized approach in extensive simulations on a large-scale, real-world network topology. Our results indicate that the two algorithms can compete with centralized approaches in terms of solution quality but require less global knowledge and are magnitudes faster (more than 100x).
Keywords: distributed management; service coordination; network coordination; nfv; softwarization; orchestration

Self-Driving Network and Service Coordination Using Deep Reinforcement Learning - Schneider, Stefan Balthasar; Manzoor, Adnan; Qarawlus, Haydar; Schellenberg, Rafael; Karl, Holger; Khalili, Ramin; Hecker, Artur (IEEE International Conference on Network and Service Management (CNSM))
Modern services comprise interconnected components, e.g., microservices in a service mesh, that can scale and run on multiple nodes across the network on demand. To process incoming traffic, service components have to be instantiated and traffic assigned to these instances, taking capacities and changing demands into account. This challenge is usually solved with custom approaches designed by experts. While this typically works well for the considered scenario, the models often rely on unrealistic assumptions or on knowledge that is not available in practice (e.g., a priori knowledge). We propose a novel deep reinforcement learning approach that learns how to best coordinate services and is geared towards realistic assumptions. It interacts with the network and relies on available, possibly delayed monitoring information. Rather than defining a complex model or an algorithm how to achieve an objective, our model-free approach adapts to various objectives and traffic patterns. An agent is trained offline without expert knowledge and then applied online with minimal overhead. Compared to a state-of-the-art heuristic, it significantly improves flow throughput and overall network utility on real-world network topologies and traffic traces. It also learns to optimize different objectives, generalizes to scenarios with unseen, stochastic traffic patterns, and scales to large real-world networks.
Keywords: self-driving networks; self-learning; network coordination; service coordination; reinforcement learning; deep learning; nfv

Augmented and Virtual Reality Object Repository for Rapid Prototyping - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Proceedings of the 8th International Working Conference on Human-Centered Software Engineering (HCSE'20))

Automatic Fairness Testing of Machine Learning Models - Sharma, Arnab; Wehrheim, Heike (Proceedings of the 32th IFIP International Conference on Testing Software and Systems (ICTSS))

“On-The-Fly” Calculation of the Vibrational Sum-Frequency Generation Spectrum at the Air-Water Interface - Ojha, Deepak; Kühne, Thomas D. (Molecules)
In the present work, we provide an electronic structure based method for the “on-the-fly” determination of vibrational sum frequency generation (v-SFG) spectra. The predictive power of this scheme is demonstrated at the air-water interface. While the instantaneous fluctuations in dipole moment are obtained using the maximally localized Wannier functions, the fluctuations in polarizability are approximated to be proportional to the second moment of Wannier functions. The spectrum henceforth obtained captures the signatures of hydrogen bond stretching, bending, as well as low-frequency librational modes.

Disordered crystals from first principles II: Transport coefficients - Kühne, Thomas; Heske, Julian Joachim; Prodan, Emil (Annals of Physics)
This is the second part of a project on the foundations of first-principle calculations of the electron transport in crystals at finite temperatures, aiming at a predictive first-principles platform that combines ab-initio molecular dynamics (AIMD) and a finite-temperature Kubo-formula with dissipation for thermally disordered crystalline phases. The latter are encoded in an ergodic dynamical system (Ω,G,dP), where Ω is the configuration space of the atomic degrees of freedom, G is the space group acting on Ω and dP is the ergodic Gibbs measure relative to the G-action. We first demonstrate how to pass from the continuum Kohn–Sham theory to a discrete atomic-orbitals based formalism without breaking the covariance of the physical observables w.r.t. (Ω,G,dP). Then we show how to implement the Kubo-formula, investigate its self-averaging property and derive an optimal finite-volume approximation for it. We also describe a numerical innovation that made possible AIMD simulations with longer orbits and elaborate on the details of our simulations. Lastly, we present numerical results on the transport coefficients of crystal silicon at different temperatures.